2018
DOI: 10.1016/j.seizure.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Narrative analysis of written accounts about living with epileptic or psychogenic nonepileptic seizures

Abstract: This study is based on a narrative analysis of individuals' written accounts of living with epilepsy (n = 29) or psychogenic non-epileptic seizures (n = 20, PNES). Narrative analysis looks at both the content and structure of the personal account. We used a form of narrative analysis that allowed us to identify common story lines, otherwise known as narrative typologies, potentially characteristic of these patient groups. Different narrative typologies were described and compared between writers with the two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Here emerges the fact that the patient's willingness and ability to take part in future procedures is essential. While some patients express the intent to seek professional help and "fight" the disorder, others might feel lost, powerless or accept their presumable lack of control over PNES [38]. Finally, factors like psychiatric comorbidities, lack of motivation or an avoidant coping style could lead to high levels of non-adherence [39][40][41][42][43].…”
Section: Pnesbeing Lost In a Labyrinthmentioning
confidence: 99%
See 1 more Smart Citation
“…Here emerges the fact that the patient's willingness and ability to take part in future procedures is essential. While some patients express the intent to seek professional help and "fight" the disorder, others might feel lost, powerless or accept their presumable lack of control over PNES [38]. Finally, factors like psychiatric comorbidities, lack of motivation or an avoidant coping style could lead to high levels of non-adherence [39][40][41][42][43].…”
Section: Pnesbeing Lost In a Labyrinthmentioning
confidence: 99%
“…Physicians may believe that driving should be restricted in PNES as in the case of epilepsy, further limiting patient independence [49]. Besides, patients living with PNES might themselves associate their condition with personal losses or having to strive for being an appreciated member of society [38]. This, in turn, can lead to feelings of entrapment, social isolation and potentially worsen the course of PNES, which are strongly linked to psychosocial factors.…”
Section: Pnesbeing Lost In a Labyrinthmentioning
confidence: 99%
“…The correlation between PTQ scores and mSBCS, and the moderate correlation between PTQ and seizure frequency may suggest some repetitive thoughts relate to seizure activity, though this is only an inference. Previous qualitative studies comparing reported experiences of PWPNES and PWE provide some initial insights, but no studies have focussed on the content of repetitive thoughts specifically [43,44]. The identification of themes for RNT would be an interesting focus for future research and could help better to specify targets for psychological therapies.…”
Section: Limitationsmentioning
confidence: 99%
“…There is interesting work emerging from the study of qualitative communication patterns between patients and HCPs showing distinct patterns between PNES and epilepsy. 7,8 In addition, conversations between HCPs and patients with PNES can involve language that inadvertently distances or even alienates patients, with words revealing HCP beliefs or biases 9 such as telling patients they don’t have “real seizures,” “everything is normal,” or that “nothing is wrong” despite the patient feeling physically quite unwell and unable to function. Studies also show that physicians use ambiguous words within their notes that imply a less than certain diagnosis which can lead patients to search for more opinions.…”
Section: Commentarymentioning
confidence: 99%